Paradigm of Shifting the Meaning of the Term Ahlu Al-Dzikri in the Digital World - Shahbal, Ammar Ali; Nirwana, Andri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The concept of ahl al-dzikr in the Qur'an is a normative as well as an epistemological category that functions as a reference for religious authorities in Islam. In the classical Islamic tradition, ahl al-dzikr is understood as a subject of knowledge that gains legitimacy through scientific competence, interpretation methodology, sanad transmission, and institutional recognition. However, the development of the digital space has significantly reconfigured the mechanisms of formation and legitimacy of religious authorities. Social media and online da'wah platforms encourage a shift in authority from a scientific basis to a visibility, performativity, and algorithmic basis, thus giving rise to an implicit redefinition of the meaning of ahl al-dzikr. This article aims to critically analyze the shift in the meaning of ahl al-dzikr in the digital era as a paradigmatic transformation of Islamic religious authority, not just a change in the medium of da'wah. This research uses a qualitative approach with a conceptual-critical design through a systematic literature study of normative-classical sources and contemporary studies of digital Islam. The analysis was carried out by integrating critical discourse analysis and contextual hermeneutics to read the tension between the normative meaning of the Qur'an and the practice of religious authority in the digital space. The results of the study show that the shift in the meaning of ahl al-dzikr has implications for the fragmentation of authority, the relativization of religious references, and the blurring of the boundary between scientific authority and religious popularity. Although the digital space opens up opportunities for wider religious participation, this condition poses epistemological and theological problems related to the legitimacy of religious authority. This article offers a rearticulation of ahl al-dzikr as an epistemological concept that remains rooted in Islamic scientific principles, as well as adaptive to digital reality, in order to strengthen responsible digital religious literacy.